The brominated flame retardants TBP-AE and TBP-DBPE antagonize the chicken androgen receptor and act as potential endocrine disrupters in chicken LMH cells. Issue 8 (December 2015) - Asnake, Solomon; Pradhan, Ajay; Kharlyngdoh, Joubert Banjop; Modig, Carina; Olsson, Per-Erik
Abstract Increased exposure of birds to endocrine disrupting compounds has resulted in developmental and reproductive dysfunctions. We have recently identified the flame retardants, allyl-2, 4, 6-tribromophenyl ether (TBP-AE), 2-3-dibromopropyl-2, 4, 6-tribromophenyl ether (TBP-DBPE) and the TBP-DBPE metabolite 2-bromoallyl-2, 4, 6-tribromophenyl ether (TBP-BAE) as antagonists to both the human androgen receptor (AR) and the zebrafish AR. In the present study, we aimed at determining whether these compounds also interact with the chicken AR. In silico modeling studies showed that TBP-AE, TBP-BAE and TBP-DBPE were able to dock into to the chicken AR ligand-binding pocket. In vitro transfection assays revealed that all three brominated compounds acted as chicken AR antagonists, inhibiting testosterone induced AR activation. In addition, qRT-PCR studies confirmed that they act as AR antagonists and demonstrated that they also alter gene expression patterns of apoptotic, anti-apoptotic, drug metabolizing and amino acid transporter genes. These studies, using chicken LMH cells, suggest that TBP-AE, TBP-BAE and TBP-DBPE are potential endocrine disrupters in chicken.